Soil greenhouse gas emissions from different land utilization types in Western Kenya - Kibet, Esphorn; Musafiri, Collins M.; Kiboi, Milka; Macharia, Joseph; Ng’etich, Onesmus K.; Kosgei, David K.; Mulianga, Betty; Okoti, Michael; Zeila, Abdirahman; Ngetich, Felix Kipchirchir (Frontiers in Soil Science, 2022)
There is a vast data gap for the National and regional greenhouse gas (GHG) budget from different smallholder land utilization types in Kenya and sub-Saharan Africa (SSA) at large. Quantifying soil GHG, i.e., methane(CH4), carbon dioxide (CO2), and nitrous oxide (N2O) emissions from smallholder land utilization types, is essential in filling the data gap. We quantified soil GHG emissions from different land utilization types in Western Kenya. We conducted a 26-soil GHG sampling campaign from the different land utilization types. The five land utilization types include 1) Agroforestry M (Agroforestry Markhamia lutea and sorghum), 2) sole sorghum (sorghum monocrop), 3) Agroforestry L (Sorghum and Leucaena leucocephala), 4) sole maize (maize monocrop), and 5) grazing land. The soil GHG fluxes varied across the land utilization types for all three GHGs (p≤0.0001). We observed the lowest CH4 uptake under grazing land (-0.35 kg CH4-C ha-1) and the highest under sole maize -1.05 kg CH4-C ha-1. We recorded the lowest soil CO2 emissions under sole maize, 6509.86 kg CO2-C ha-1, and the highest under grazing land, 14400.75 kg CO2-C ha-1. The results showed the lowest soil N2O fluxes under grazing land, 0.69 kg N2O-Nha-1, and the highest under agroforestry L at 2.48 kg N2O-N ha-1. The main drivers of soil GHG fluxes were soil bulk density, soil organic carbon, soil moisture, clay content, and root production. The yield-scale N2O fluxes ranged from 0.35 g N2O-N kg−1under sole maize to 4.90 g N2O-N kg−1 grain yields under Agroforestry L. Nevertheless, our findings on the influence of land utilization types on soil GHG fluxes and yield-scaled N2O emissions are within previous studies in SSA, including Kenya, thus fundamental in filling the national and regional data of emissions budget. The findings are pivotal to policymakers in developing low-carbon development across land utilization types for smallholders farming systems.